Legal System Disclosure Experiences of Young Adult Children Exposed to Domestic Violence - Kahovec, Amie E. (Journal of interpersonal violence, 2023)
Children exposed to domestic violence (DV) disclose their experiences to a variety of people, including informal (e.g., peers), formal (e.g., doctors), and legal (e.g., police) support systems. Legal system disclosure is more common than formal system disclosure yet remains understudied leaving unanswered questions about the nature of those who choose to disclose and factors that influence their disclosure decision. Guided by communication privacy management theory and Johnson’s typology of domestic violence (DV), this study addressed gaps in the CEDV literature through a theoretical thematic analysis of the DV exposure and legal system disclosure experiences of 25 young adults exposed to father-mother-perpetrated DV during their childhood. Findings from this study show that half of the participants had no legal system disclosure (n = 12; nondisclosers) and half had at least some legal system disclosure (n = 13; disclosers). Varying types of violence exposure and levels of exposure were factors that impacted youths’ decisions to disclose to legal systems. Escalation of violence was a key factor that drove legal system disclosure, but other factors including how the young adults and their communities perceived their fathers, the match between the youth’s goals for disclosure and the outcomes upon disclosing, along with family privacy norms and family boundaries were influential in guiding decision making over time. This study has implications for practitioners working with DV-exposed youth, as our findings unpack the conditions under which youth choose to (not) disclose, the factors influencing these decisions, and how the responses and reactions from legal support systems inform future disclosure decisions.